The Plastic Arts for Fine Motor Development in Second Graders from The Republica Dominicana School - Almeyda Cortes, Johana Marcela; González Bejarano, Sonia Viviana (Rastros Rostros, 2021)
Introduction: This article frames the role of the plastic arts in the strengthening of children’s fine motor skill, starts by making known the importance of the arts in education and the competences they develop. Then, fine motor skill is described analyzed in light of different pedagogues and the artistic techniques to work that contribute to the improvement of fine motor processes in students, according to their stages, age and evolutionary characteristics. Methodology: The methodology used is also shown referring to an investigation of a quantitative nature, using as a research technique: direct observation and as information-gathering tools: a diagnostic test applied to thirty second grade students and a questionnaire applied to eight teachers; such information was later analyzed in light of some categories and subcategories of analysis. Results: Once the data collected has been analyzed it became clear that students have fine motor difficulties, so what, they require activities that develop, Encourage and improve their motor skills, that’s how, were proposed and carried out plastic arts techniques that would contribute to this process. Conclusions: Finally, if a good stimulation is given and development of fine motor skills through art, from the child's earliest age in a sequential way, progressive and coordinated, we will get prevention of potential difficulties and reduction of learning disorders in the classroom.
Keywords: Fine Arts; Aesthetic Appreciation; Communication; Constructivism; Visual-Motor Coordination; Fine Motor Skills; Sensitivity